Preservation of Sundanese Ethnic Culture by Young Generation in the Era of Globalization - Amalia, Rosaria Mita; Sidiq, Inu Isnaeni; Darmayanti, Nani (International Journal of Psychosocial Rehabilitation, 2020)
Sundanese cultural values are one of Indonesian local culture that must be preserved. Students, as agents in society, are part of the community and expected to be the successor of the Sundanese culture. This study shows how the role of young people, such as students in English Literature, Faculty of Cultural Sciences, Universitas Padjadjaran perform particular preservation of Sundanese culture in language, dance and musical instruments. The methods used are quantitative and qualitative. Data collection conducted by distributing questionnaires to research objects that have been determined in accordance with the research topic. The objects of the research is English Literature students in Faculty of Cultural Sciences (FIB), Universitas Padjadjaran. The students come from class of 2018, and they have an age range between 18-22 years.Tthey are divided into two categories, namely the Sundanese (SS), and not the Sundanese (BSS). For the SS category of respondents ,there are 40 students, as well as the BSS category, 40 students. The results of the questionnaire are used as a basis in analyzing data and indicators for analysis to determine how the students of the Department of English Literature at FIB, Unpad maintain and preserve Sundanese culture. The results shows that students as respondents to the questionnaire code "Sunda" conduct the biggest defense in terms of using the Sundanese pattern of language. While the students as respondents to the questionnaire code “Non-Sunda” also give the biggest contribution in watching Sundanese dance performance.